2023
DOI: 10.1038/s41522-023-00389-1
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with ubiquitous protist Blastocystis ST1 ameliorates DSS-induced colitis and promotes beneficial microbiota and immune outcomes

Abstract: Blastocystis is a species complex that exhibits extensive genetic diversity, evidenced by its classification into several genetically distinct subtypes (ST). Although several studies have shown the relationships between a specific subtype and gut microbiota, there is no study to show the effect of the ubiquitous Blastocystis ST1 on the gut microbiota and host health. Here, we show that Blastocystis ST1 colonization increased the proportion of beneficial bacteria Alloprevotella and Akkermansia, and induced Th2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Some studies have demonstrated that ST1 has beneficial effects on the host gut microbiome and immune system. Deng et al showed that colonization with Blastocystis ST1 could increase the levels of Alloprevotella and Akkermansia , which are beneficial bacteria for gut health, in a murine model [ 73 ]. Blastocystis ST3, another very common subtype, has been shown to cause an increase in beneficial bacteria such as Bacillota (syn.…”
Section: Blastocystis and The Gut Microbiomementioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have demonstrated that ST1 has beneficial effects on the host gut microbiome and immune system. Deng et al showed that colonization with Blastocystis ST1 could increase the levels of Alloprevotella and Akkermansia , which are beneficial bacteria for gut health, in a murine model [ 73 ]. Blastocystis ST3, another very common subtype, has been shown to cause an increase in beneficial bacteria such as Bacillota (syn.…”
Section: Blastocystis and The Gut Microbiomementioning
confidence: 99%
“…These data indicate subtype-specific effects of Blastocystis on immune modulation. Moreover, regarding host–microbiome interactions, the increase in diverse bacteria in the gut microbiota of Blastocystis ST1 and ST4 carriers causes SCFA production, which is important for the immune system overall and its modulation [ 73 , 96 ].…”
Section: Blastocystis and The Gut Microbiomementioning
confidence: 99%
See 2 more Smart Citations
“…The role of Blastocystis in the human microbiome, whether it is harmful or beneficial, is still the subject of debate, despite its widespread colonization among the population. The outcome of gastrointestinal tract colonization may be influenced by factors such as the composition of gut bacterial communities, the host's immune status, and, notably, the genetic background of various Blastocystis subtypes (STs), with subtypes ST1 and ST4 being beneficial and ST7 pathogenic (Ajjampur et al , 2016; Yason et al , 2019; Deng et al , 2023a,b). There is limited information on how these protists interact with the gut immune system during intestinal colonization.…”
Section: Introductionmentioning
confidence: 99%